مقاصد سور القرآن عند البقاعي (ت 885 هـ) دراسة نظرية تطبيقية: The Objectives of Qur'anic Chapters According to Al-Baqā’i (D. 885 H): A Theoretical and Applicative Study - Cica Maulina Beni (البصيرة: مجلة الدراسات الإسلامية, 2024)
This research belongs to the field of Maqāṣid al-Suwar (Objectives of Qur'anic Chapters) and is titled: "The Objectives of Qur'anic Chapters According to al-Baqā’ī (d. 885 H): A Theoretical and Applicative Study." The aim is to collect the Maqāṣid al-Suwar from al-Baqā’ī’s two works, Musā'id al-Naẓr and Niẓām al-Durar, as well as from other scholars who have studied the objectives of the chapters. The research also examines how various interpreters (mufassirun) derive the Maqāṣid al-Suwar from the Qur'an and compares their methodologies. This study employs three approaches: inductive, analytical, and comparative. Among the key findings are: (1) Maqāṣid al-Suwar is a term later defined by al-Baqā’ī as a science that reveals the purposes of the Qur'anic chapters; (2) Maqāṣid al-Suwar is a discipline that deserves careful study, as it plays a vital role in Qur'anic interpretation and greatly facilitates the understanding of the Qur'an's meanings; (3) According to al-Baqā’ī, the Maqāṣid al-Suwar can be categorized into three types: matters of creed, law, and ethics; (4) The objectives of the chapters have a significant impact on other Islamic sciences, such as Tafsir (exegesis), by enhancing the understanding of Qur'anic interpretation, including munāsabāt (correlations between chapters), and legal reasoning (istinbāṭ), as this knowledge serves as a foundation for understanding the objectives of the Qur'anic chapters.